2016
DOI: 10.1016/j.jhep.2016.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Reversion of disease manifestations after HCV eradication

Abstract: Chronic infection with the hepatitis C virus (HCV) may lead to hepatic fibrosis and eventually cirrhosis, at which stage, patients have a substantial risk of liver failure, hepatocellular carcinoma (HCC) and liver-related death. Moreover, HCV infection is associated with several extrahepatic manifestations which impact the quality of life and increase the non-liver-related mortality rate. For patients with compensated liver disease, interferon (IFN)-based antiviral therapy has been a treatment option for over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0
12

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(121 citation statements)
references
References 103 publications
(140 reference statements)
6
103
0
12
Order By: Relevance
“…However, it has been demonstrated that the achievement of a sustained virological response after interferon-based therapy is associated with lower rates of hepatocellular carcinoma and with lower rates of hepatic decompensation [9,10] . A regression of fibrosis after viral eradication has also been reported [11] .…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…However, it has been demonstrated that the achievement of a sustained virological response after interferon-based therapy is associated with lower rates of hepatocellular carcinoma and with lower rates of hepatic decompensation [9,10] . A regression of fibrosis after viral eradication has also been reported [11] .…”
Section: Introductionmentioning
confidence: 84%
“…Only 37.8% of patients were naïve, and 11% had liver graft cirrhosis. All patients were Child-Pugh A class at the start of the treatment and the median MELD score was 7 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). At the initiation of therapy, mean bilirubin level was 1.06 ± 0.27 mg/dL, mean platelet count was 117,788 ± 50,546/mm 3 , and mean albumin level was 4,140 ± 424 mg/dL.…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary evidence has shown reduced HCC recurrence rates after resection and reduced death from all causes in HCC patients. [39][40][41][42][43][44] As the new therapies become incorporated into many aspects of HCC treatment, it is likely that they will enhance survival rates for HCC ablation, resection, and transplant.…”
Section: Effective New Antiviral Therapies: Are They Now Part Of Hepamentioning
confidence: 99%
“…Furthermore, the risk of complications persists even after achieving SVR, although there is evidence demonstrating improvement in liver function tests after using DAAs [10,11] . Also, even after achieving SVR, re-infection is a possibility that can occur in 10%-15% of patients, especially in individuals at risk, such as intravenous drug users [12] .…”
Section: Introductionmentioning
confidence: 99%